Network traffic monitor for IDS in IoT - Bolatti, Diego; Todt, Carolina; Scappini, Reinaldo; Gramajo, Sergio (My University, 2022)
As network services and IoT technologies rapidly evolve, in literature there are many anomalies detection proposals based on datasets to deal with cybersecurity threats. Most of this proposal uses structured data classification and they can recognize with a certain degree of accuracy whether a type of traffic is “anomalous” or not. Even what kind of anomaly it has. Nevertheless, previous works do not clearly indicate the technical methodology to set up the data gathered scenarios. As a main contribution, we are going to show a detailed deployment IoT traffic monitor ready for intelligent network traffic classification. Monitoring and sniffers are an essential concept in network management as it helps network operators to determine the network behavior and status of its components. Anomaly detection also depends on monitoring for decision-making. Thus, this paper will describe the creation of a portable network traffic monitor for IoT using Docker container and bridge networking with SDN.
Keywords: Network monitoring; IoT; IDS; SDN